2009
DOI: 10.1073/pnas.0806117106
|View full text |Cite
|
Sign up to set email alerts
|

Direct and specific inactivation of protein tyrosine kinases in the Src and FGFR families by reversible cysteine oxidation

Abstract: Accumulating evidence suggests that protein tyrosine phosphorylation-based signaling pathways are under the regulation of reactive oxygen species. Although protein tyrosine phosphatases are directly regulated by reversible oxidation, it is not clear whether protein tyrosine kinases (PTKs) are also directly regulated by reduction/oxidation (redox). In this study we report a mechanism of direct oxidative inactivation specific for the PTKs in the Src and fibroblast growth factor receptor (FGFR) families, key enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 35 publications
6
122
2
Order By: Relevance
“…Subsequent studies by Senga et al (2000) identified a number of cysteine residues in Src necessary for the enzymes stability and transformative ability. Giannoni et al (2005) focused on Cys245 and Cys487 which were demonstrated to undergo intramolecular Although these studies support a model whereby Src is activated in response to ROS, data consistent with an inhibitory role for ROS in Src activity has also been proffered by Kemble et al (2009). In contrast to the majority of published studies, yet echoing the earlier results of Cunnick et al (1998), Kemble proposes that, upon oxidation, intermolecular disulfide bridges form between Cys277 residues on two Src molecules, resulting in inactive Src dimers.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Subsequent studies by Senga et al (2000) identified a number of cysteine residues in Src necessary for the enzymes stability and transformative ability. Giannoni et al (2005) focused on Cys245 and Cys487 which were demonstrated to undergo intramolecular Although these studies support a model whereby Src is activated in response to ROS, data consistent with an inhibitory role for ROS in Src activity has also been proffered by Kemble et al (2009). In contrast to the majority of published studies, yet echoing the earlier results of Cunnick et al (1998), Kemble proposes that, upon oxidation, intermolecular disulfide bridges form between Cys277 residues on two Src molecules, resulting in inactive Src dimers.…”
Section: Discussioncontrasting
confidence: 54%
“…This is in contrast to the cell-free assays used by Kemble et al (2009), in which a redox-inactivation of Src was also observed. However Tang Irrespective of its consequence for Src kinase activity, the susceptibility of Src to redox regulation is a characteristic shared by other members of the Src family kinases (SFK).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Reactive oxygen species, such as superoxide and hydrogen peroxide, serve as secondary messengers to regulate signaling pathways of certain growth factors and cell adhesion. A number of studies have suggested that cysteine modification of c-Src plays an important role for the reactive oxygen speciesmediated signal transductions; however, whether c-Src is activated or inactivated by oxidation remains unclear (31). Upon cell adhesion, c-Src is activated by the formation of an intramolecular S-S bond between Cys 245 and Cys 487 , which are highly conserved residues among the Src family kinases and are localized in the SH2 domain and kinase domain, respectively (17).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mitogen-activated protein kinase kinase kinase 1, a member of the MAP3K family, oxidation selectively induces glutathionylation of Cys 1238 near the conserved GXGXXG(or S/A) motif (i.e., P loop) in the kinase subdomain I (i.e., GLGAFSSC 1238 ) that is known to directly bind ATP (15). As for Src, a recent paper showed that oxidation induced the formation of a homodimer via an intermolecular disulfide bond between two Cys 277 in the middle of the conserved P loop (i.e., GQGC 277 FG in rat Src) (33). In both cases above, oxidation of a specific cysteine in the kinase domain inactivates the kinases, which is fully reversible upon treatment with a reducing agent.…”
Section: Discussionmentioning
confidence: 99%